What Research Says About MOOCs – An Explorative Content Analysis - Zawacki-Richter, Olaf; Bozkurt, Aras; Alturki, Uthman; Aldraiweesh, Ahmed (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Since the first offering of a Massive Open Online Course (MOOC) in 2008, the body of literature on this new phenomenon of open learning has grown tremendously. In this regard, this article intends to identify and map patterns in research on MOOCs by reviewing 362 empirical articles published in peer-reviewed journals from 2008 to 2015. For the purposes of this study, a text-mining tool was used to analyse the content of the published research journal articles and to reveal the major themes and concepts covered in the publications. The findings reveal that the MOOC literature generally focuses on four lines of research: (a) the potential and challenges of MOOCs for universities; (b) MOOC platforms; (c) learners and content in MOOCs; and (d) the quality of MOOCs and instructional design issues. Prospective researchers may use these results to gain an overview of this emerging field, as well as to explore potential research directions.